2009
DOI: 10.1002/bbb.131
|View full text |Cite
|
Sign up to set email alerts
|

Projected mature technology scenarios for conversion of cellulosic biomass to ethanol with coproduction thermochemical fuels, power, and/or animal feed protein

Abstract: Seven process designs for producing ethanol and several coproducts from switchgrass are evaluated:four involving combinations of ethanol, thermochemical fuels (including Fischer-Tropsch liquids, hydrogen, and methane) and/or power, and three coproducing animal feed protein. Material and energy balances -resulting from detailed Aspen Plus models -are reported and used to estimate processing costs and perform discounted cash fl ow analysis to assess plant profi tability. In these mature technology designs, fossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 12 publications
(23 reference statements)
0
47
0
2
Order By: Relevance
“…The enzyme production costs are tightly interlinked with the protein yield of cellulase in the fermentation broth as well as the enzyme activity. Therefore, continuous efforts towards the cost reduction of enzymes and increasing the overall protein production have been routed towards exploring hyperactive microbial strains, efficient fermentation techniques and cost-effective recovery systems (Laser et al 2009). Use of different mutagenic agents for microbial strain improvement and fermentation processes was demonstrated by Parekh et al (2000).…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme production costs are tightly interlinked with the protein yield of cellulase in the fermentation broth as well as the enzyme activity. Therefore, continuous efforts towards the cost reduction of enzymes and increasing the overall protein production have been routed towards exploring hyperactive microbial strains, efficient fermentation techniques and cost-effective recovery systems (Laser et al 2009). Use of different mutagenic agents for microbial strain improvement and fermentation processes was demonstrated by Parekh et al (2000).…”
Section: Introductionmentioning
confidence: 99%
“…Further, there are advantages in the handling, combustion, and transportation of gaseous fuel over solid fuels which are not reflected in the costs. In several studies, moisture content was identified as an important factor in thermochemical conversion and combined heat and power processes due to an increased heat of vaporization (Caputo et al 2005;Phillips et al 2007;Laser et al 2009;Dutta et al 2011;Gonzalez et al 2012;Verma et al 2012). …”
Section: Delivered Cost Per Million Btumentioning
confidence: 99%
“…Both the biological (hydrolysis-fermentation) and thermochemical (gasification -synthesis) processes require the use of advanced, high-efficiency equipment for electricity production, to satisfy process requirements and provide surplus electricity for sale [89,90]. However, advanced equipment such as BIG/ CC systems [84,91,92] have high capital costs per unit electricity [19,93]. Economies of scale achieved through integration of electricity production in second-generation biofuel processes with electricity production in adjacent industrial facilities can reduce capital investment per unit of electricity substantially [24,90,92,94 -96].…”
Section: Energy Integration Between Lignocellulosic Conversion Procesmentioning
confidence: 99%